PI and T9-SPI: New Predictive Factors for Increased Kyphosis of the Thoracolumbar Junction in Thoracolumbar/Lumbar Adolescent Idiopathic Scoliosis - Lin, XiaoLong; Zhu, Jie; Sha, Weiping; Yan, Fei; Wang, Liming; Qiu, Yong (Frontiers in Pediatrics, 2020)
Objectives: Studies have demonstrated that there is an increased thoracolumbar junction sagittal Cobb angle (TLJS) in thoracolumbar/lumbar adolescent idiopathic scoliosis (AIS) patients. The objectives were to ascertain the correlations between the spinopelvic alignments and TLJS and to explore potential predictive factors for hyperkyphotic TLJS in the sagittal plane in thoracolumbar/lumbar AIS. Methods: A total of 114 AIS patients with thoracolumbar/lumbar curve were included. Cobb angle, apical vertebrae rotation (AVR), thoracic kyphosis (TK), TLJS, lumbar lordosis (LL), pelvic incidence (PI), sacral slope (SS), pelvic tilt (PT), T1-spinopelvic inclination (T1-SPI) and T9-spinopelvic inclination (T9-SPI) were measured. After patients were organized into 2 subgroups based on TLJS, all parameters were compared between the 2 groups. Correlation analysis and multiple linear regression analysis were performed between the radiologic measurements and TLJS in all patients. Results: There was a significant difference between the non-kyphotic group and kyphotic group in mean Nash-Moe grade, TK, T9-SPI, PI and SS. Correlation analysis showed that LL, PI and SS were inversely associated with TLJS. TK, T9-SPI and Nash-Moe grade were positively related to TLJS. The multiple linear regression analysis showed that TLJS could be predicted by the equation TLJS =−2.322+5.585×Nash-Moe grade+0.687×T9-SPI−0.208×PI, with an adjusted R2 of 0.410. Conclusion: TLJS was positively correlated with greater AVR in the coronal plane, greater T9-SPI in the sagittal plane and inversely associated with PI among patients with thoracolumbar/lumbar scoliosis. Spine surgeons should pay more attention to the degree of AVR, T9-SPI and PI when dealing with thoracolumbar/lumbar scoliosis with thoracolumbar junction kyphosis.